Community-based ecotourism: Its socio-economic impacts at Boabeng-Fiema Monkey Sanctuary, Ghana - Eshun Gabriel; Tonto Joycelyn Naana Pokuaa (Bulletin of Geography. Socio-Economic Series)
There is a lacuna in literature from Western Africa on how issue of participation influence socio-economic impacts at ecotourism destinations. This paper investigates the socio-economic impacts of ecotourism based on Boabeng- Fiema Monkey Sanctuary in Ghana. The paper is based on primary data generated from Boabeng and Fiema communities. Seventy mainly opened-ended questionnaires were administered face-to-face to purposively selected residents from the two communities, alongside, in-depth interviews with the management of the Sanctuary and focus group with purposively selected individuals from Boabeng and Fiema. The study reveals that the residents of the communities face burgeoning challenges such as shrinking livelihood options, inadequate involvement of community in the ecotourism, poor state of the visitor centre, inadequate government support and poor roads.